(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT : Kumo beach is one of the busiest beaches in North Halmahera, Kumo beach is also one of the island cluster of islands in front of Tobelo town which can be reached Â± 5 minutes by motorized boat. Island Kumo is located right in front of Tobelo town with a beach shaded by trees and a beautiful white sand and the sea is clear, strong and strong and suitable for activities such as snorkeling, boating and others, the choice of the local tourists because of its beautiful scenery access close from Tobelo town. Unfortunately, all the advantages of a tourist beach Kumo untapped and managed properly, it is very necessary for the implementation of policies that seriously by policymakers and implementers alike. The research was analyzed using qualitative descriptive method. Thus, the details can be drawn that the data analysis technique that is performed is after the data are collected, then the next data will be combined, depicted in narrative form sentences by providing interpretation or interpretation based on direct observation conducted by researchers with samples of the object existing research or respondent which exists. The results of this research show that the efforts made by the Department of Tourism and culture of North Halmahera District has not been able to explore and manage the attraction beach Kumo well because they said there are various factors that hamper policy makers and implementers in implementing the policy of tourism development on the island of Kumo. Keywords: Policy Implementation, Development, Attractions.